De afvoer van de Noor (Zuid-Limbrug) : periode 1992 - 1997 - Dijksma, R.; van Lanen, H.A.J.; Ackerman, W.J. (Wageningen: Landbouwuniversiteit Wageningen, 1998)
"R. Dijksma; H.A.J. van Lanen; W.J. Ackerman... et al."